The Effect of Restaurant Atmosphere, Product Quality, and Price on Consumer Satisfaction at Mie Samyu Restaurant, Sumberkemba Village, Pakuniran District - Hayatul Millah; Ferry Vijaylani; Abdul Komar (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
In the current era of globalization, competition in the business world is getting fiercer, this requires every organization to be able to expand its organizational performance in order to compete in the competition. Organizations must be able to understand the needs and desires of their consumers. In this way, organizations must plan serious areas of strength in a procedure to meet their customer satisfaction and survive in business competition. The culinary industry or known as the food industry is one of the rapidly growing business fields and is currently facing very tight competition. The restaurant atmosphere variable does not have a partial effect on consumer satisfaction with a value of t count (0.576) < t table (1.684). The product quality variable has a partial effect on consumer satisfaction with a value of t count (3.184) > t table (1.684). The price variable has a partial effect on consumer satisfaction with a value of t count (3.704) > t table (1.684).